Sterically wrapping of multi-resonant fluorophores: an effective strategy to suppress concentration quenching and spectral broadening - Xiaofeng, Luo; Dongdong, Zhang; Lian, Duan; Yuewei, Zhang (Frontiers in Chemistry, 2023)
Multiple resonance (MR) emitters are promising for the next-generation wide color gamut organic light-emitting diodes (OLEDs) with narrowband emissions; however, they still face intractable challenges such as concentration-induced emission quenching, exciton annihilation, and spectral broadening. In this concept, we focus on an advanced molecular design strategy called "sterically wrapping of MR fluorophores" to address the above issues. By isolating the MR emission core using bulky substituents, intermolecular interactions can be significantly suppressed to eliminate the formation of unfavorable species. Consequently, using the newly designed emitters, optimized MR-OLEDs can achieve high external quantum efficiencies of > 40% while maintaining extremely small full width at half maxima (FWHMs) of < 25 nm over a wide range of concentrations (1-20 wt%). This strategy may shed light on the design of efficient MR emitters, which provides more room for tuning the dopant concentrations under the premise of high-efficiencies and small FWHMs, accelerating the practical application of MR-OLEDs.